Impact of active smoking on the immature platelet fraction and its relationship with the extent of coronary artery disease. (18th January 2020) - Nardin, Matteo; Verdoia, Monica; Negro, Federica; Rolla, Roberta; Tonon, Francesco; De Luca, Giuseppe
Abstract: Introduction: Smoking represents a major cardiovascular risk factor, due to the induction of oxidative stress and low‐grade, continuous, inflammation that contribute to promote atherothrombosis. However, the mechanisms leading to increased platelet aggregability associated with smoking are only partially defined. A potential role has been hypothesized for immature platelets, a younger and potentially more reactive fraction, previously associated with the main determinants of coronary artery disease (CAD). Therefore, the aim of our study was to define the impact of smoking on the immature platelet fraction (IPF) and its relationship with prevalence and extent of coronary artery disease. Methods: We enrolled a cohort of consecutive patients undergoing coronary angiography in a single centre. Significant CAD was defined as at least 1 vessel stenosis >50%, while severe CAD was defined as left main and/or three‐vessel disease. IPF was measured at admission by routine blood cell count (Sysmex XE‐2100). Results: We included in our study 2553 patients who were divided according to smoking status (active smokers: 512; nonactive smokers: 2041). Smokers were younger, more frequent males, with lower rate of diabetes mellitus, previous PCI and previous CABG ( P < .001, respectively) and were in treatment less often with ARB, BB, nitrates, statins, ASA, clopidogrel, CCB and diuretics ( P < .001, respectively) as compared to nonactive smokers. Higher percentage of smokers was observed in patients with higher IPF values, and at multivariate analysis, active smoking resulted as an independent predictor of higher IPF (adjusted OR [95% CI] = 1.59[1.03‐2.45], P = .035). Among smokers, higher IPF was associated with lower ejection fraction ( P = .034), percentage of acute coronary syndrome ( P = .002) and platelet count ( P < .001) compared to ones with lower IPF. However, the IPF (according to quartiles values) was not associated with the prevalence and extent of CAD (82.5%, 80.4%, 86.1% and 80.9%, from 1st to 4th quartile, respectively, adjusted OR[95% CI] = 0.98[0.79‐1.23], P = .89) and severe CAD (31%, 31.1%, 39.1% and 35.2%, from 1st to 4th quartile, respectively, adjusted OR[95% CI] = 1.03[0.86‐1.23], P = .76). Conclusion: The present study shows an independent association between active smoking and the levels of immature platelet fraction in patients undergoing coronary angiography. However, among active smokers, IPF did not result as an independent predictor of CAD or severe CAD.